The Horn of Moran / 2. - Forman, Mark, 1964- (Adventurers wanted, 2011)
Sixteen-year-old wizard-in-training Alex Taylor and his band of fellow adventurers battle a goblin army, navigate an enchanted forest, and try to solve the sphinx's riddle in their quest to find the lost Horn of Moran and return it to Norsland before the nation erupts in war.